Mass Media in Political Education of University Students: A Study on Perceptions of National Leadership - Azhar, Arsel Himma; Amelia, Dina; Anisa, Yuliani Nur (Proceedings Series on Social Sciences & Humanities, 2025)
The mass media, especially social media, plays an important role in the political education of students in today's digital age. The rapid and widespread accessibility of political information allows students to develop political awareness and form perceptions of national leadership. This study aims to analyze the role of the media in political education for students, focusing on how their perceptions of the quality of national leadership are shaped through media consumption. Using a literature review approach with a descriptive qualitative method, the research data was obtained through an analysis of academic literature from ten relevant sources discussing media, political education, and national leadership. The results of the study indicate that the intensity of social media use is positively correlated with the level of students' political understanding. Additionally, digital literacy plays a crucial role in determining the accuracy of students' political perceptions, while diversifying information sources enriches their political perspectives. However, misinformation and information bias remain serious challenges that must be addressed through strengthening media literacy. This study emphasizes the need for synergy between the mass media, educational institutions, and political parties in shaping holistic political education based on democratic values. In conclusion, the mass media has great potential in building a politically aware, critical, and moral younger generation, provided it is supported by adequate digital literacy and access to credible information.